Implementation of fractional electric potential using genetic algorithms - Jesus, Isabel S. (2019)
A fresh look of several phenomena present in electrical systems induced an approach based in the fractional calculus (FC) viewpoint. The problem of point multipoles with electrical charges is an important subject in the field of electromagnetism. In this work, it is applied the concept of FC to implement the electrical potential of fractional order through a genetic algorithm (GA) optimization scheme. The work is complemented by analyzing the locus of charge versus position distribution of the required electrical charges.